Avaliação da atividade fotocatalítica das nanoestruturas de hexaniobato de potássio após esfoliação e reempilhamento do material - Costa, Katiane Judy Batista da (2018)
Lamellar niobate K4Nb6O17 was synthesized by the solid state method and resulted in the trihydrate phase, exhibiting orthorhombic unit cell. K4Nb6O17·3H2O was protonated with HNO3 solution and then exfoliated with an expanding agent (TBAOH). The colloidal suspension obtained from the exfoliation underwent pH variation for the morphological study of the nanosheets. After adjusting the pHs, the nanosheets restacking process was performed with the desired structural characteristics (tabular or coiled). Two methods of restacking were developed in this work, with the intention of obtaining a satisfactory yield of the restack material. X-ray diffraction (XRD), thermogravimetric analysis (TG / DTA), absorption spectroscopy in the ultraviolet and visible (UV-Vis) region, infrared spectroscopy (FTIR), surface area analysis by BET method and scanning electron microscopy (SEM). The XRD results showed that the repopulated materials showed low organization in the long range, and peaks referring to the tabular and rolled structural morphology. The FTIR spectra of the reworked materials presented vibrational modes related to the less pronounced distorted octahedrons [NbO6]. The BET analysis indicated that the restack material had a higher surface area in relation to the initial material, and mesoporous characteristics. The methodology-2 developed in this work obtained better performance than the methodology-1, but did not maintain the desired structural characteristics. In the photocatalytic tests, the efficiency of the photocatalysts was influenced, according to: the surface area, which was not a significant parameter in the evaluation of the discoloration efficiency of C-K4RT9; the morphology of the nano-structures in nanorrolos of the material C-K4RT10, that resulted in the low photocatalytic activity due to characteristics associated with the high recombination rate of the photogenerated electron-hole pairs, as well as the shadow effect; the calcination of the C-K4RT10 repotted material, which influenced the increased discoloration efficiency, resulting from the elimination of substances (TBA+), which blocked access to the active sites present on the surface.